Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1186/s13063-016-1517-8
|View full text |Cite
|
Sign up to set email alerts
|

One-layer versus two-layer duct-to-mucosa pancreaticojejunostomy after pancreaticoduodenectomy: study protocol for a randomized controlled trial

Abstract: BackgroundAlthough various pancreaticojejunal duct-to-mucosa anastomosis methods have been developed to reduce the postoperative risks of pancreaticoduodenectomy, pancreatic fistula remains the most serious complication with a high incident rate. The aim of this study is to compare the safety and effectiveness of one-layer and two-layer duct-to-mucosa pancreaticojejunostomy in patients undergoing pancreaticoduodenectomy.Methods/designIn this study, adult patients who sign consent forms will be recruited and sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…According to the literature search, a greater focus on single-layer PJ has been reported in China, [8,[12][13][14] and the incidence of POPF and other complications was lower in single-layer PJ compared with double-layer in some studies. [14][15][16][17] Single-layer anastomosis is deemed simpler, faster, and less traumatic to the pancreas than double-layer PJ; however, there are no randomized controlled trials (RCTs) to validate this superiority. Furthermore, even in single-layer PJ, there are continuous and interrupted techniques, and no clinical controlled studies have been reported for these two suturing methods, while similar RCTs have been reported for the small intestine, mitral valve, and obstetric tract surgery.…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature search, a greater focus on single-layer PJ has been reported in China, [8,[12][13][14] and the incidence of POPF and other complications was lower in single-layer PJ compared with double-layer in some studies. [14][15][16][17] Single-layer anastomosis is deemed simpler, faster, and less traumatic to the pancreas than double-layer PJ; however, there are no randomized controlled trials (RCTs) to validate this superiority. Furthermore, even in single-layer PJ, there are continuous and interrupted techniques, and no clinical controlled studies have been reported for these two suturing methods, while similar RCTs have been reported for the small intestine, mitral valve, and obstetric tract surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Another publication showed that single layer sutures, going from the edge of the stump to the MPD prevent pancreatic fistula better than sutures passing only through a part of the pancreatic parenchyma [39]. The advantages of single-and double-layer anastomoses are about to be assessed in prospective randomized trials [40].…”
Section: Modifications Of the Duct-to-mucosa Techniquementioning
confidence: 99%